PEMIKIRAN SYEIKH ‘ALĪ JUM‘AH DALAM MANHAJ PEMFATWAAN: SATU SOROTAN AWAL: Sheikh ‘Alī Jum‘ah’s Thoughts in Fatwa Method: A Preliminary Review - Yaacob, Wan Ahmad Zuhairi; Abdullah, Luqman; Syed Jaafar, Syed Mohd Jeffri (Jurnal Syariah, 2023)
Fatwa is an explanation regarding the determination of a syariah law issued by an individual who has the authority over it. Fatwas need to be implemented seriously and systematically to preserve the validity of laws that achieve maqāsid al-sharī‘ah (objectives of shari‘ah). To answer a current question, a fatwa that wants to be issued must be based on an accurate understanding of the text and a perfect knowledge of the real world. However, some of the fatwas issued by him have sparked controversy in the discourse of syariah law. Therefore, this study aims to look at the methodology and the process of fatwa issuance initiated by Sheikh ‘Alī Jum‘ah. This study uses a qualitative method approach, which is by analyzing data and information collected from various sources, including Sheikh ‘Alī Jum‘ah’s writings, the works of past and contemporary scholars, journals, and websites. Generally, the study found that the methodology and fatwa issuance process practiced by Sheikh ‘Alī Jum‘ah is not different from what other Islamic scholars have articulated. However, a series of his approaches have resulted in different legal answers and may bring about controversy in Islamic legal discourse.